Pengaruh Time Budget Pressure dan Risiko Audit Terhadap Penghentian Prematur Atas Prosedur Audit Pada Kantor Akuntan Publik di Kota Makassar - Eva Marin Sambo; Ariputra, Edhan (Insan Cita Bongaya Research Journal, 2024)
The purpose of this study is to determine the effect of Time Budget Pressure and Audit Risk on Premature Termination of Audit Procedures at Public Accounting Firms in Makassar City. Data collection uses primary data obtained from questionnaires. Determination of the sample using the saturated sample method, so that the sample in this study were 40 respondents. The results of the questionnaire have been tested for validity and reliability, and have also been tested for classic assumptions in the form of normality assumptions, heteroscedasticity assumptions, and multicollinearity assumptions. Methods of data analysis using multiple regression analysis. The research results show that Time Budget Pressure has a positive and significant effect on Premature Termination of Audit Procedures and Audit Risk does not have a positive and significant effect on Premature Termination of Audit Procedures.